2021
DOI: 10.3390/ijms22052453
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Gastrointestinal and Immunomodulatory Effects of the Novel Probiotic Bacillus subtilis DE111

Abstract: Probiotics make up a large and growing segment of the commercial market of dietary supplements and are touted as offering a variety of human health benefits. Some of the purported positive impacts of probiotics include, but are not limited to, stabilization of the gut microbiota, prevention of gastrointestinal disorders and modulation of the host immune system. Current research suggests that the immunomodulatory effects of probiotics are strain-specific and vary in mode of action. Here, we examined the immunom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
(61 reference statements)
2
17
0
2
Order By: Relevance
“…For example, the B. subtilis strain MB40 has been shown to be safe and support GI health in a randomized, double-blind, placebo-controlled trial of 100 healthy adults [ 17 , 35 ]. Additionally, B. inaquosorum DE111 supplementation has been shown to be safe in both adult and pediatric human subjects [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Altogether, these studies provide a large body of clinical evidence that Bacillaceae spp., including B. subtilis , are safe for human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the B. subtilis strain MB40 has been shown to be safe and support GI health in a randomized, double-blind, placebo-controlled trial of 100 healthy adults [ 17 , 35 ]. Additionally, B. inaquosorum DE111 supplementation has been shown to be safe in both adult and pediatric human subjects [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Altogether, these studies provide a large body of clinical evidence that Bacillaceae spp., including B. subtilis , are safe for human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several clinical and animal trials have demonstrated the protection of B. subtilis against Salmonella and other enteropathogenic bacteria in broilers through the load reduction in intestinal tracts, improvement of the growth performance, and immune responses ( Wu et al., 2018 ; Sokale et al., 2019 ; Abudabos et al., 2020 ). Nevertheless, the action modes of probiotic B. subtilis are in a strain-specific manner ( Freedman et al., 2021 ), which makes it necessary to investigate the potential protection against Salmonella infection in poultry farming.…”
Section: Introductionmentioning
confidence: 99%
“…inaquosorum DE111; 2.5 × 10 9 CFU/day) for 4 weeks showed no difference in participant self-reported GI symptoms compared to placebo groups. 50 , 51 It is noteworthy that the aforementioned studies and ours were dissimilar on several aspects that may contribute to the contrast in results. These include differences in supplementation length (4 weeks vs. 6 weeks), questionnaires used, as well as definition and analysis of efficacy outcomes (odds ratio vs. mean scores).…”
Section: Discussionmentioning
confidence: 66%